"Programmed Cell Death: A Process of Death for Survival" – How Far Terminology Pertinent for Cell Death in Unicellular Organisms. (January 2018) - Pandey, Shiv Shanker; Singh, Samer; Pathak, Chandramani; Tiwari, Budhi Sagar
Programmed cell death (PCD) is genetically regulated phenomenon of selective elimination of target cells that are either under pathological conditions or unwanted for organism's normal growth and development due to other reasons. The process although being genetically controlled is physiological in nature that renders some hallmarks like blebs in the cell membrane, lobe formation in nuclear membrane, DNA nicks resulting to DNA ladder of 200 bp, and downstream activation of caspases. Moreover, as the process refers to the death of "targeted cell", the term is exclusively suitable for multicellular organisms. Number of reports advocate similar type of cell death process in unicellular organisms. As cell death in unicellular organisms is also reflected by the signature of PCD obtained in metazoans, such cell death has been grouped under the broad category of PCD. It is pertinent to mention that by definition a unicellular organism is made of a single cell wherein it carries out all of its life processes. Using the term "Programmed Cell Death" with a preset "survival strategy of the organism" for unicellular organisms looks misnomer. Therefore, this correspondence argues and requests recommendation committee on cell death to revisit for the nomenclature of the cell death process in the unicellular organisms.